2017
DOI: 10.1039/c7cp01768e
|View full text |Cite
|
Sign up to set email alerts
|

Energy flow in peptides after UV photoexcitation of backbone linkages

Abstract: We report on the dissociation channels after UV photoexcitation of peptide cations tagged with 18-crown-6 ether (CE). The model peptides chosen for study were singly protonated (Ala)-Pro (n = 1, 2, 3) and Pro-Pro (Ala = alanine, Pro = proline) that all contain at least one tertiary amide group with high absorption cross section at 210 nm (5.90 eV). Statistical dissociation was identified from the loss of CE, a process occuring remotely from the initial site of excitation, and therefore requiring flow of energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…It should be noted that the absorbance band of the peptide bond is rather broad, and thus, for example, 205 nm is often chosen as a more convenient absorption wavelength for concentration measurements in solution 54 . Similarly, in gas‐phase work, it has been shown that the absorption cross section at 210 nm is very appreciable 19 . UVPD experiments of proteins at 213 nm thus combine the high‐absorption cross section of the protein backbone, while minimizing absorption by atmospheric gases, and are thus conducive to elevated pressure conditions compatible with ion mobility spectrometry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the absorbance band of the peptide bond is rather broad, and thus, for example, 205 nm is often chosen as a more convenient absorption wavelength for concentration measurements in solution 54 . Similarly, in gas‐phase work, it has been shown that the absorption cross section at 210 nm is very appreciable 19 . UVPD experiments of proteins at 213 nm thus combine the high‐absorption cross section of the protein backbone, while minimizing absorption by atmospheric gases, and are thus conducive to elevated pressure conditions compatible with ion mobility spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…UVPD, in particular, has proven to be a very versatile tool to study the primary, tertiary, and quaternary structures of proteins and protein complexes 9,10 . UVPD begins when the ion absorbs UV light, producing an electronically excited state of the ion 18–20 . The electronically excited ion then may undergo a variety of relaxation processes, or it may dissociate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation supports the notion that two distinct fragmentation mechanisms, statistical vs. nonstatistical fragmentation, are operative in the UVPD process. [31][32][33][34] Statistical fragmentation occurs when the electronic excitation energy is converted into vibrational excitation (internal conversion) followed by intramolecular vibrational energy redistribution (IVR) and subsequent dissociation of the peptide backbone into b/y ions according to the mobile proton model. 35,36 Importantly, H/D scrambling is an inevitable prelude to fragmentation of protonated peptides by statistical fragmentation processes.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the region between 3.7 and 4.7 eV (Vis to near-UVA), photofragmentation is clearly non-statistical with production of the m/z 135 photofragment being photochemically enhanced. 42,[72][73][74][75][76] 4. Discussion…”
Section: Uv Photofragmentation Of Ab•h +mentioning
confidence: 99%